The benefits of the myofascial release technique in the treatment of chronic low back pain: a review study (Research, Society and Development, 2023)
The fascia is a tissue that surrounds the muscle to allow sliding, in other words, the mechanical element of force transmission is the muscle fascia, and it is present in every muscle chain. Meanwhile, pain in the lumbar region is a very specific symptom for each patient, and it is closely related to professional and postural activities, ranging from socioeconomic, occupational, psychological and even demographic factors. The aim was to seek evidence from scientific studies on the benefits of the myofascial release technique in the treatment of chronic low back pain. This is an integrative literature review research. The research sources were obtained through a bibliographic survey, using articles published in the following databases: BVS Brasil, PubMed and Scielo. The results of the studies suggest that the myofascial release technique can be a choice for physiotherapeutic treatment, mainly in reducing pain and increasing the specificities of the patient's functional status. It is concluded that myofascial release acts directly on the muscle tissue, since there is a liquid between the fascia and the muscle that allows sliding, and therefore, myofascial release will deal exactly with the quality of this sliding between the fascia and the muscle.